Structural and Morphological Investigations on Shape Memory CuZnAl Alloys - Zengin, R.; Kayal, N. (Polish Acad Sciences Inst Physics, 2010)
Macroscopic, structural and morphological features of shape memory CuZnAl alloys were examined by elongation parameter measurement, X-ray diffraction and optical metallography. It has been seen that shape initiating temperature (T(z)) is greater than austenite start temperature (A(s)). According to the X-ray diffraction, it has been defined that transformation happened from austenite phase to martensite phase as L2(1) -> M18R and martensite crystal lattice has been in monoclinic structure. In metallographic observations the grain structures were observed, then plate martensites, V-type martensite structures, twin-like bands, precipitation phases were found. In addition, it has been observed that a-sediment phase has occurred in specimens with ageing at austenitic phase condition.
Keywords: Martensite